The Ashgate research companion to Chinese foreign policy - Kavalski, Emilian (Rethinking Asia and international relations, 2012)
"The Ashgate Research Companion to Chinese Foreign Policy draws out the full range of topics and issues that characterise China's external affairs. The volume is intended to provide an overview of Chinese foreign policy that will be relevant both to experts in the field as well as those that are just starting to grapple with Beijing's international outlook. The investigation of Chinese foreign policy offered by the volume is divided into seven parts:- Part I focuses on the historical evolution of Chinese foreign policy by detailing the specific traditions and the altering paradigms of Beijing's external outlook proffered for the explanation and understanding of Chinese foreign policy- Part II discusses the different analytical perspectives proffered for the explanation and understanding of Chinese foreign policy- Part III considers the domestic sources of Chinese foreign policy- Part IV analyses the international impact of Beijing's outreach- Part V of the volume begins the exploration of China's relations with specific international actors- Part VI investigates the regional interactions of Chinese foreign policy- Part VII of the volume draws attention to several issues impacting both the practice and the understanding of Chinese foreign policyThis Companion draws a vivid picture of the full spectrum of topics, issues, and relationships that define China's international interactions. The collection therefore provides a relevant point of departure for anyone interested in learning about Beijing's external affairs. Owing to the wide range of themes and ideas, this volume is essential reading for students of Chinese foreign policy"--Provided by publisher.